Missed opportunities for delivering nutrition interventions in first 1000 days of life in India: insights from the National Family Health Survey, 2006 and 2016. Issue 2 (24th February 2021) - Nguyen, Phuong Hong; Avula, Rasmi; Tran, Lan Mai; Sethi, Vani; Kumar, Alok; Baswal, Dinesh; Hajeebhoy, Nemat; Ranjan, Alok; Menon, Purnima
Abstract : Objectives: Existing health and community nutrition systems have the potential to deliver many nutrition interventions. However, the coverage of nutrition interventions across the delivery platforms of these systems has not been uniform. We (1) examined the opportunity gaps between delivery platforms and corresponding nutrition interventions through the continuum of care in India between 2006 and 2016 and and (2) assessed inequalities in these opportunity gaps. Methods: We used two rounds of the National Family Health Survey data from 2005 to 2006 and 2015–2016 (n=36 850 and 190 898 mother–child dyads, respectively). We examine the opportunity gaps over time for seven nutrition interventions and their associated delivery platforms at national and state levels. We assessed equality and changes in equality between 2006 and 2016 for opportunity gaps by education, residence, socioeconomic status (SES), public and private platforms. Results: Coverage of nutrition interventions was consistently lower than the reach of their associated delivery platforms; opportunity gaps ranging from 9 to 32 percentage points (pp) during the pregnancy, 17 pp during delivery and 9–26 pp during childhood in 2006. Between 2006 and 2016, coverage improved for most indicators, but coverage increases for nutrition interventions was lower than for associated delivery platforms. The opportunity gaps were larger among women with higher education (22–57 pp in 2016), higher SES status and living in urban areas (23–57 pp), despite higher coverage of most interventions and the delivery platforms among these groups. Opportunity gaps vary tremendously by state with the highest gaps observed in Tripura, Andaman and Nicobar islands, and Punjab for different indicators. Conclusions: India's progress in coverage of health and nutrition interventions in the last decade is promising, but both opportunity and equality gaps remained. It is critical to close these gaps by addressing policy and programmatic delivery systems bottlenecks to achieve universal coverage for both health and nutrition within the delivery system.